The efficiency of the Community Dental Service in England: a data envelopment analysis - Buck D (Blackwell Synergy, 2000)
To assess the efficiency with which health authorities’ Community Dental Services provide dental care in England. Methods: A data envelopment analysis of inputs (hours worked by dental officers, therapists, hygienists and others) and outputs (screening, treatment, prevention) of the Community Dental Service (CDS) was conducted. Relative efficiency ratings of the CDS by health authority were further analysed in order to identify external factors which effect efficiency and are outside the control of the Community Dental Service.